2016
DOI: 10.1111/eea.12428
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning of the generalist herbivore Trialeurodes vaporariorum to greenhouse monocultures and its subsequent performance on wild polycultures

Abstract: Generalist herbivores can face many challenges when choosing their host plant. This can be particularly difficult if their choice and performance are affected by host experience. Greenhouse whitefly, Trialeurodes vaporariorum Westwood (Hemiptera: Aleyrodidae), is an invasive generalist herbivore, which has established in year‐round greenhouses at northern latitudes where it cannot overwinter outdoors. It mainly uses crops such as cucumber (Cucumis sativus L.), tomato (Solanum lycopersicum L.), and ornamentals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
0
2
1
Order By: Relevance
“…Our results from the performance test conducted under controlled conditions showed that weeds such as Bidens aurea exhibited higher populations than commercial crops. However, this behavior was not observed under field conditions in the study area; this is in contrast to Ovčarenko et al [29], who argued that whiteflies prefer weeds surrounding crops rather than the crops inside greenhouses. The factors that could affect the performance of the insect depend on the physical and chemical properties of the plant, such as trichome density [36,38], secondary metabolites [39], and thick cuticles [1].…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Our results from the performance test conducted under controlled conditions showed that weeds such as Bidens aurea exhibited higher populations than commercial crops. However, this behavior was not observed under field conditions in the study area; this is in contrast to Ovčarenko et al [29], who argued that whiteflies prefer weeds surrounding crops rather than the crops inside greenhouses. The factors that could affect the performance of the insect depend on the physical and chemical properties of the plant, such as trichome density [36,38], secondary metabolites [39], and thick cuticles [1].…”
Section: Discussioncontrasting
confidence: 92%
“…Luciana, 7742, and Mistral. No preadaptation conditions of the whitefly according to Ovčarenko et al [29]. To avoid possible selection bias, the variety of tomatoes was changed in the test.…”
Section: Insect Rearingmentioning
confidence: 99%
See 1 more Smart Citation